Pengaruh Model Pembelajaran Savi Terhadap Hasil Belajar Siswa Pada Tema 1 Subtema 1 Organ Gerak Hewan Kelas V SD Negeri 097320 Serapuh - Naomi Srirejeki Harianja; Yanti Arasi Sidabutar; Sudirman T P Lumbangaol (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purpose and influence of the SAVI Learning Model. This research was conducted at SD Negeri 097320 Serapuh. Quantitative research using experimental techniques is the methodology used. This research uses a Pre-Experimental "One Group Pretest-Posttest" design. There were 28 fifth grade children at SD Negeri 097320 Serapuh who were the samples for this research. The analysis shows that the average results of the experimental class support the research hypothesis that has been tested and have quite a large influence on the data that has been studied.